On orders of approximation of the generalized Nikol’skiу-Besov class in Lorentz spaces - Akishуev, G. (Ye.A.Buketov Karaganda State University Publishing house, 2013)
In this paper Lorentz space is considered with mixed norm. Definition of the generalized Nikol’skiy-Besov classes is given. The main results of the paper are the estimates of the order of approximation of functions of the generalized Nikol’skiy-Besov class by partial sums of multiply series Fourier constructed with harmonics from the hyperbolic cross.
Лоренц кеңістігінде жалпыланған Никольский–Бесов класын жуықтаудың реті жайлы
О порядках приближения обобщенного класса Никольского–Бесова в пространстве Лоренца
Keywords: Lorentz space; Nikol’skiy-Besov class; approximation of function; hyperbolic cross